The Effect of Deficit Irrigation and Regulated Deficit Irrigation on Yield and Water Productivity of the Watermelon - N. Bahremand; H. Aroiee; A. Aien (مجله آب و خاک)
Introduction Watermelon (Citrullus lanatus) is a widely recognized product with high demand, nutritional value, and export potential worldwide. Since the ultimate goal of agricultural production systems is to maximize plant yield, providing sufficient water to the plant is one of the most critical factors influencing yield. Therefore, investigating the effects of water limitation is an essential and undeniable necessity. On the other hand, deficit irrigation has been introduced as an approach to increase water productivity. Therefore, it is essential to consider the effects of this water-saving method on plant production, which highlights the need for further research. Deficit irrigation involves supplying only a portion of the plant's water requirements, while regulated deficit irrigation is a specific type of deficit irrigation that can be applied in various ways, such as irrigation based on growth stages, or allocating water to stages that are more sensitive to drought. It is important to recognize that plant response to water deficit depends on several factors, including climatic conditions, plant type, the intensity and method of deficit irrigation application, soil condition, and management practices.